Assessing the transport connectivity of urban territories, based on intermodal transport accessibility - Morozov, Aleksandr S.; Kontsevik, Georgii I.; Shmeleva, Irina A.; Schneider, Lasse; Zakharenko, Nikita; Budenny, Semen; Mityagin, Sergey A. (Frontiers in Built Environment, 2023)
By 2050, around 70% of people will live in urban areas. According to 11.2 target of UN SDG "Sustainable cities and communities" to provide access to safe, affordable, accessible and sustainable transport systems for all, the aim of the paper presented was to investigate accessibility and connectivity of urban territories by sustainable transport systems in Saint-Petersburg, the largest Northern-West city by population more 5 million in Russia. The main emphasis of the research was directed on transport infrastructure, which can be seen as sustainable, including public transport and cycling. The quality of life in a large city is determined by the ability to get from one destination to another quickly and efficiently. To implement this task a methodology has been developed to assess the connectivity and accessibility of urban areas. The method, based on a multimodal transport graph and the dimensionality reduction method T-SNE, is presented as an example of assessing accessibility and connectivity by car, by public transport and by bike in different districts of Saint-Petersburg. The results are presented as heat maps from the most populated city area and graphs with clusters of city blocks presented as points. It is clear indicated that different areas of the city are connected through time values differently depending on the types of transportation. The method can be used to make urban planning decisions, decisions about the provision of urban infrastructure, allows for ongoing monitoring of the situation and filling in the gaps.